Clinical efficacy of Ni-Ti memory alloy four-corner arthrodesis concentrator in the treatment of scaphoid nonunion advanced collapse: a follow-up of over 10 years - Baochuang Qi; Minzheng Guo; Chen Meng; Teng Wang; Chuan Li; Yongqing Xu (Journal of Plastic Surgery and Hand Surgery)
Purpose: Exploring the therapeutic effects of Ni-Ti shape memory alloy four-corner arthrodesis concentrator (NT-FCAC) in treating scaphoid nonunion advanced collapse (SNAC) and providing a decade-long follow-up report.